Seawater Chemistry and Hydrothermal Controls on the Cenozoic Osmium Cycle - Joachim A. R. Katchinoff; Drew D. Syverson; Noah J. Planavsky; Erica S. J. Evans; Alan D. Rooney (Geophysical Research Letters)
Abstract Osmium isotope ratios are a key tool to track changes in global weathering and carbon cycle evolution through time. Long‐term changes in seawater Os isotope records over the Cenozoic have been used to argue for changes in weathering from increased uplift, leading to long‐term global cooling. Sulfide mineral precipitation during hydrothermal circulation traps the majority of mantle‐derived Os within mid‐ocean ridge (MOR) hydrothermal systems. Building from evidence that the amount of sulfide mineral precipitation in the subseafloor of MOR systems is related to the amount of sulfate and calcium in seawater, we show that as seawater chemistry changed through time, so too has the extent of hydrothermal sulfide formation and the global Os cycle. With currently estimated changes in seawater Ca/SO4 ratios, the observed progressive increase in seawater Os isotope values through the Cenozoic can be linked to changes in seawater chemistry—instead of a major shift in continental weathering processes.